Fusarium Infection in a Kidney Transplant Recipient Successfully Treated with Voriconazole - Ahmed M. Alkhunaizi; Ali M. Bazzi; Ali A. Rabaan; Elwaleed A. Ahmed (Case Reports in Infectious Diseases)
Fusarium infections in solid-organ transplant recipients are rare and carry high mortality. We report a case of a kidney transplant recipient who developed infection with Fusarium species. The patient received treatment with oral voriconazole for five months with good response.